Examining the Impact of Internal Control and Internal Audit on the Trustworthiness of Accounting Information Systems: A Literature Review - Suharyuno; Ranti melasari; Elsya Fitrianisa (Acman: Accounting and Management Journal, 2025)
The objective of this research is to examine how internal control and internal audit affect the reliability of accounting information systems (AIS), drawing insights from 15 national and international journal articles. The review reveals that the majority of these sources emphasize a positive and statistically significant relationship between internal control mechanisms and internal audit functions on AIS reliability. Well-structured internal control systems contribute to accurate, consistent, and trustworthy system output, while also minimizing mistakes and fraudulent activities. Moreover, when internal audits are carried out independently, they enhance transparency, streamline reporting, and increase institutional accountability. Some studies further highlight an indirect influence through enhanced fraud detection and improved quality of financial reporting. Hence, the collaborative interaction between internal audit and internal control is pivotal to achieving dependable and high-quality accounting information systems. Strengthening these components not only improves the integrity, transparency, and accuracy of accounting data but also builds trust among stakeholders. Additionally, ongoing training for internal auditors is essential to effectively address emerging risks and challenges. By focusing on these aspects, organizations can significantly improve their decision-making processes and optimize resource management, thereby enhancing overall operational effectiveness.